Monolithic Papain-Immobilized Enzyme Reactors for Automated Structural Characterization of Monoclonal Antibodies - Rinaldi, Francesca; Tengattini, Sara; Brusotti, Gloria; Tripodo, Giuseppe; Peters, Benjamin; Temporini, Caterina; Massolini, Gabriella; Calleri, Enrica (Frontiers in Molecular Biosciences, 2021)
The characterization of monoclonal antibodies (mAbs) requires laborious and time-consuming sample preparation steps before the liquid chromatography-mass spectrometry (LC-MS) analysis. Middle-up approaches entailing the use of specific proteases (papain, IdeS, etc.) emerged as practical and informative methods for mAb characterization. This work reports the development of immobilized enzyme reactors (IMERs) based on papain able to support mAb analytical characterization. Two monolithic IMERs were prepared by the covalent immobilization of papain on different supports, both functionalized via epoxy groups: a Chromolith® WP300 Epoxy silica from Merck KGaA and a polymerized high internal phase emulsion (polyHIPE) material synthesized by our research group. The two bioreactors were included in an in-flow system and characterized in terms of immobilization yield, kinetics, activity and stability using Nα-Benzoyl-L-arginine ethyl ester (BAEE) as a standard substrate. Moreover, the two bioreactors were tested towards a standard mAb, namely Rituximab (RTX). An on-line platform for mAb sample preparation and analysis with minimal operator manipulation was developed with both IMERs, allowing to reduce enzyme consumption and to improve repeatability compared to in-batch reactions. The site-specificity of papain was maintained after its immobilization on silica and polyHIPE monolithic supports and the two IMERs were successfully applied to RTX digestion for its structural characterization by LC-MS. The main pros and cons of the two supports for the present application were described.